Integrating Social Perception and Economic Valuation for Riparian Zone Preservation: Evidence from Kiliti Watershed, Ethiopia - Haileyesus Gelaw Asres (International Journal of Environmental Planning and Development Architecture, 2026)
Riparian zones play a crucial role in maintaining watershed health by providing ecosystem services such as water filtration, erosion control, biodiversity conservation, and aesthetic and cultural benefits to surrounding communities. Despite their importance, riparian areas in many developing countries are increasingly degraded due to agricultural expansion, grazing pressure, and settlement encroachment. This study integrates social perception analysis with economic valuation to assess riparian zone preservation in the Kiliti Watershed, Northwestern Ethiopia. Data was collected from 200 households across three sub-basins (Amen, Kiliti, and Gurdala) using structured questionnaires. Social perceptions of riparian ecological quality were measured using a semantic differential scale, while economic valuation was conducted using a willingness-to-accept (WTA) contingent valuation approach to estimate compensation required for participation in conservation initiatives. The results show a strong positive correlation between community perception scores and ecological quality indices (r = 0.81, p < 0.01), indicating that local communities accurately perceive riparian environmental conditions. The mean WTA for conservation participation was estimated at 3,400 Ethiopian Birr per household per year. Regression analysis revealed that education level, farm size, livestock ownership, and off-farm income significantly influenced both perception scores and WTA values. Households with higher environmental awareness and diversified income sources required lower compensation. The findings demonstrate that integrating social perception with economic valuation provides a comprehensive and cost-effective framework for participatory riparian management, supporting ecologically sustainable and socially acceptable conservation policies in the Kiliti Watershed and similar socio-ecological contexts.
Keywords: Ethiopia; Riparian zones; conservation; economic valuation; ecosystem services; social perception